2020
DOI: 10.3390/antibiotics9060293
|View full text |Cite
|
Sign up to set email alerts
|

The Puzzle of Coccoid Forms of Helicobacter pylori: Beyond Basic Science

Abstract: Helicobacter pylori (H. pylori) may enter a non-replicative, non-culturable, low metabolically active state, the so-called coccoid form, to survive in extreme environmental conditions. Since coccoid forms are not susceptible to antibiotics, they could represent a cause of therapy failure even in the absence of antibiotic resistance, i.e., relapse within one year. Furthermore, coccoid forms may colonize and infect the gastric mucosa in animal models and induce specific antibodies in animals and humans. Their de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 91 publications
0
29
0
3
Order By: Relevance
“…No statistically significant differences were found regarding the frequency of each morphological shape between samples collected at 48 and 64 h, and between 64 and 72 h samples ( Figure 1D ). However, a significant decrease in the number of bacillary ( p = 0.003) and an increase in the number of coccoid H. pylori ( p = 0.012) were observed in samples collected at 72 h when compared to those obtained at 48 h. This observation suggests that coccoid forms are viable but non-culturable ( Ierardi et al, 2020 ), as there was no alteration in the frequency of viable bacteria, assessed by the LIVE/DEAD assay, at this time point. As an ancillary analysis, we checked the morphology of H. pylori grown in F12-cholesterol by SEM ( Supplementary Figure 3 ), which confirmed that the bacillary shape was predominant at all time points, with the U-shape and coccoid bacteria becoming noticeable in the 72 h cultures.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…No statistically significant differences were found regarding the frequency of each morphological shape between samples collected at 48 and 64 h, and between 64 and 72 h samples ( Figure 1D ). However, a significant decrease in the number of bacillary ( p = 0.003) and an increase in the number of coccoid H. pylori ( p = 0.012) were observed in samples collected at 72 h when compared to those obtained at 48 h. This observation suggests that coccoid forms are viable but non-culturable ( Ierardi et al, 2020 ), as there was no alteration in the frequency of viable bacteria, assessed by the LIVE/DEAD assay, at this time point. As an ancillary analysis, we checked the morphology of H. pylori grown in F12-cholesterol by SEM ( Supplementary Figure 3 ), which confirmed that the bacillary shape was predominant at all time points, with the U-shape and coccoid bacteria becoming noticeable in the 72 h cultures.…”
Section: Resultsmentioning
confidence: 93%
“…Like previously described for other bacterial culture media ( Kusters et al, 1997 ; Adams et al, 2003 ; Olofsson et al, 2010 ), we observed a morphological change of H. pylori from the bacillary to the coccoid forms throughout bacterial growth. The significant decrease in the number of CFUs at 72 h was not mirrored by the loss of bacterial viability using the LIVE/DEAD assay, likely due to the fact that coccoid forms are viable but non-culturable bacteria, with minimal metabolic activity, and preserved membrane and genetic material integrities ( Adams et al, 2003 ; Ierardi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that coccoid forms consist of viable but non-culturable coccoid (VBNC) and non-viable degenerative coccoid forms ( 34 ). The VBNC form has minimal metabolic activity and can survive during stress conditions such as in the presence of antibiotics, which may be one of the causes of treatment failure ( 35 ). However, potent plant preparations that act through multiple mechanisms on the bacterium and could be consumed for long-term treatment due to their safety may successfully kill the bacterium including the dormant form.…”
Section: Discussionmentioning
confidence: 99%
“…Strong inhibition of acid secretion could promote its transition from the coccoid form to the spiral-shaped form. 32 Accordingly, it is most important to increase gastric pH in order to increase the eradication rate, especially in the first-line triple therapy containing AMPC and CAM. The high eradication rate of P-CAB-based first-line triple therapy supports this theory.…”
Section: Discussionmentioning
confidence: 99%